Mucosal Abnormalities in Children With Congenital Chloride Diarrhea—An Underestimated Phenotypic Feature? - Kurteva, Elena; Lindley, Keith J.; Hill, Susan M.; Köglmeier, Jutta (Frontiers in Pediatrics, 2020)
Objectives and study Congenital Chloride Diarrhoea (CCD) is a rare, autosomal recessive disorder caused by mutations in the SLC26A3 gene encoding a transmembrane chloride/bicarbonate ion exchanger mainly expressed in the apical brush border of the ileal and colonic epithelium. Life-long, secretory, chloride-rich diarrhoea, and hypochloremic, hypokalemic metabolic alkalosis are characteristic. Histological evidence of bowel inflammation is not typically described in CCD, and has only been reported in a few patients. Methods We report 4 cases of CCD who received adequate resuscitation with appropriate replacement of their fecal salt and water losses. Three had associated inflammatory bowel changes at endoscopy. The index case of CCD who developed frankly bloodstained diarrhoea aged 7 months was found to have histologically confirmed colitis at endoscopy. An electronic search of the hospital database to identify all patients with confirmed CCD was performed. A further three children underwent de novo diagnostic evaluation and treatment. A retrospective case note review was undertaken, to determine the incidence and subtype of inflammatory bowel disease (IBD) by clinical, endoscopic and histological means. Results Four children with genetically confirmed CCD were identified, two being female. The first girl had a granulomatous colitis with ulceration. She went into remission with a combination of steroids and Azathioprine. Immunosuppression was subsequently discontinued without a further flare of colitis. A second girl was found to have patchy inflammatory changes in the small bowel and focal active colitis. A third patient, a boy, demonstrated mild inflammatory changes in the small bowel with apoptotic debris and mild inflammation in the colon. A fourth patient did not develop intestinal inflammation. Conclusion Our case series highlights the potential association of CCD with panenteric inflammation. Whilst our cohort was small, CCD is rare and three out of four children referred to our tertiary referral centre were affected. Whilst early diagnosis and adequate salt replacement therapy are crucial in CCD management, the clinician should also be aware of bowel inflammation as a potential cause of failure of CCD therapy to control bowel symptomatology. Further insight is needed to understand the underlying patho-mechanism giving rise to bowel inflammation in this group.